Unmet LTC Needs in Community: A Qualitative Study of Family, Cadres, and Stakeholder Perspectives - Wardani, Yulia; Febriani, Dita Hanna; Amigo, Thomas Aquino Erjinyuare; Morales, Jeremy Godofredo C (Journal of Applied Nursing and Health, 2026)
Background: The growing older adult population in Indonesia has increased the need for community-based long-term care (LTC). However, families and community health cadres continue to face challenges in providing post-hospitalisation care, particularly in rural areas where LTC and transitional care services remain limited. This study explored the perspectives of family caregivers, cadres, and stakeholders on unmet needs and strategies to strengthen community-based LTC. Methods: A descriptive phenomenological qualitative study was conducted using purposive sampling. Fourteen participants were interviewed in face-to-face, semi-structured, in-depth interviews, and twelve stakeholders participated in a Focus Group Discussion (FGD). Data were collected in community and primary healthcare settings in Turi District, Sleman Regency, Yogyakarta, Indonesia, and analyzed using conventional content analysis with NVivo 12, and reported according to the COREQ guideline. Results: Four interconnected themes emerged from the analysis: (1) existing caregiving practices involving physical, psychosocial, and spiritual support; (2) challenges in home-based LTC related to complex health conditions, caregiver burden, and limited resources; (3) priority needs for improving LTC quality, including caregiver training, supportive equipment, and multidisciplinary collaboration; and (4) stakeholder perspectives regarding the benefits and implementation challenges of community-based transitional care services. The findings generated a conceptual framework demonstrating that caregiver empowerment, community support, accessible resources, and multidisciplinary collaboration contribute to improved LTC quality and better outcomes for older adults. Conclusion: Older adults receiving LTC in Indonesian communities experience multidimensional unmet needs that require integrated responses from families, cadres, healthcare providers, and local stakeholders. Strengthening family-centered and community-based LTC systems, caregiver education, sustainable support mechanisms, multidisciplinary collaboration, and feasible transitional care pathways is essential to improve continuity, safety, dignity, and quality of life among older adults.